Fracking and mortgage default - Christopher R. Cunningham; Kristopher Gerardi; Yannan Shen (Federal Reserve Bank of Atlanta, 2017)
This paper finds that increased hydraulic fracturing, or "fracking", along the Marcellus Formation in Pennsylvania had a significant, negative effect on mortgage credit risk. Controlling for potential endogeneity bias by utilizing the underlying geologic properties of the land as instrumental variables for fracking activity, we find that mortgages originated before the 2007 boom in shale gas, were, post-boom, significantly less likely to default in areas with greater drilling activity. The weight of evidence suggests that the greatest benefit from fracking came from strengthening the labor market, consistent with the double trigger hypothesis of mortgage default. The results also suggest that increased fracking activity raised house prices at the county-level.
Keywords: Q51; R11; G21; 330; mortgage default; hydraulic fracking; house prices; shale gas